KONFLIK LAHAN ANTARA MASYARAKAT DENGAN PT. INTI KAMPARINDO SEJAHTERA (STUDY KASUS PADA LOKASI LAHAN DI DESA DANAU LANCANG KECAMATAN TAPUNG HULU KABUPATEN KAMPAR ) - Regar, Nella; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the village Danau Lancang Kecamatan Tapung Hulu Kabupaten Kampar with the aim to obtain information about land conflicts between communities and PT. Inti Kamparindo Sejahterah. Some of the problems in this study were (1) How is the source of conflict in the village of Danau Lancang Districts Tapung Hulu Kampar district? (2) What forms of conflict that occurred in the village of Danau Lancang Districts Tapung Hulu Kampar district? (3) How to conflict resolution in the Village of Danau Lancang Districts Tapung Hulu Kampar district?. The title of this research is "Land Conflicts between communities in the village of Lancang Lake District of Hulu Tapung Kampar District". This research aims to determine how the source of conflict in the Village of Lake Lancang District of Hulu Tapung Kampar district. To determine the shape of the conflict in the Village of Lake Lancang District of Hulu Tapung Kampar district. To mengetahuai how conflict resolution efforts in the Village of Lake Lancang District of Hulu Tapung Kampar district. This research is qualitative because its nature is shaped case, which was the subject of this study is determined by those who know and are involved directly in the conflicts as much as 8 subjects land PT. Inti kamparindo Sejahtera. In colleccting the data, engineering data colleeting using observation, interviews. To analyze the problems in this study using qualitative analysis as well as well be described in descriptive in doing the writing. After pe This research has, the survey results revealed that the shape of the land conflicts between communities in the Village of Danau Lancang is a demonstration, the action of the grave themselves, the action stay and hunger and the many parties involved in the land conflicts among communities, The PT IKS, the Village Head, Member of Parliament Kampar, police Tapung Hulu, Ninik Mamak and Coordinator Demo. Source of conflict, forms of conflict and the parties involved trigger land conflicts between communities and PT. Inti Kamparindo Sejahtera in the village of Danau Lancang.Keywords: Land Conflicts, PT.IKS. Danau Lancang